PERTANGGUNGJAWABAN PERDATA ATAS WANPRESTASI DALAM PERJANJIAN JUAL BELI - Fahlevi, Muhammad Eggi; Rusli, Benni; Nazar, Jasman (Collegium Studiosum Journal, 2023)
An agreement is a legal relationship carried out by two or more parties based on an agreement to give rise to a legal effect. Agreements made together aim to achieve achievements, including in terms of trade carried out, especially in buying and selling transactions. A valid sale and purchase agreement usually cannot be canceled by either party easily without any clear reason. A sale and purchase agreement can only be canceled if there is consent from both parties who entered into the agreement. But in the sale and purchase agreement, not a few of the parties commit violations with various reasons and arguments that tend to justify why they broke the agreement or broke their promise. The agreement was made as a form of agreement between the two parties, to regulate and protect legal relations between private or civil interests. The purpose of this study is to determine civil liability for default in a sale and purchase agreement. The research method is normative juridical. Using qualitative analysis techniques. Conventionally,conventionally, civil liability arises when a party fails to fulfill contractual or non-contractual obligations that have been agreed upon. These obligations may include providing compensations as a result of customer agreements that occur due to their own negligence, the mistakes of other people who are under their responsibility, or losses caused by their negligence.